Considering The MUI Fatwa Method in Determining The Heretical Fat-wa from The Perspetive of Maqosid Sharia - Dzulkurnain, Iskandar; Asmuni, Asmuni; Kusyaeni, Kusyaeni (Eduvest - Journal of Universal Studies, 2025)
In recent years, the emergence of splinter religious sects in Indonesia has triggered considerable conflict, controversy, and social unrest. The Indonesian Ulema Council (Majelis Ulama Indonesia—MUI), as an authoritative institution consisting of scholars and religious leaders, plays a significant role in issuing fatwas to safeguard the faith and religious integrity of the Muslim community. This study aims to examine MUI’s fatwas regarding the designation of heretical sects through the lens of maqāṣid al-sharīʿah, with particular emphasis on the principle of ḥifẓ al-dīn (protection of religion). Using a qualitative descriptive approach, the research analyzes MUI’s fatwa documents and interprets them within the framework of Islamic legal theory. The findings demonstrate that MUI’s fatwas are consistent with the objectives of sharia (maqāṣid al-sharīʿah) and serve as a preventive mechanism against doctrinal deviations that may threaten religious harmony. This study underlines the importance of fatwas as a tool for religious preservation and community protection in pluralistic societies.